The Correlation Between Youth's Knowledge With Youth's Perceptions of PWHA (People With HIV/AIDS) - Oktavia, Rice Dwi; Dewi, Yulia Irvani; Utami, Sri (Poltekkes Kemenkes Jakarta III, 2022)
Students' knowledge of PWHA (People With HIV/AIDS) affects their perception of PWHA in the form of positive and negative responses. This study aims to determine the relationship between knowledge and perceptions of University of Riau students towards PWHA (People With HIV/AIDS). This study used a descriptive correlation design with a cross-sectional approach. These research subjects are 391 people who were taken based on inclusion criteria using a stratified random sampling technique—data analysis using bivariate analysis using the chi-square test. Statistical tests showed that there was a significant relationship between knowledge and perception of PWHA with a p-value (0.000) < alpha (0.05). University of Riau students' knowledge of PWHA has a significant relationship with University of Riau students' perceptions of PWHA. We firmly suggest that foundations or peer support group organizations carry out educational activities for adolescents about sexually transmitted diseases, especially HIV/AIDS.